2016
DOI: 10.1590/0100-2945-271/14
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO, FISIOLOGIA DA MATURAÇÃO E INDICADORES DO PONTO DE COLHEITA DE FRUTOS DA UMBUGUELEIRA (Spondias sp.)

Abstract: RESUMO -A umbugueleira produz frutos com amplas possibilidades de utilização que, embora subexplorados, têm grande potencial socioeconômico. Dessa forma, o objetivo deste estudo foi avaliar o desenvolvimento e a fisiologia da maturação em frutos da umbugueleira. As inflorescências foram marcadas em seis plantas, no período da antese, e o fruto (umbuguela) foi avaliado em intervalos regulares até a abscisão da planta. O ciclo de desenvolvimento da umbuguela, da antese até o início da abscisão, abrange 157 dias;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
2
10
0
9
Order By: Relevance
“…Colour parameters in the epicarp of Mexican plum showed significant (P<0.05) changes among the four ripening stages (Vargas et al, 2017), similar to that reported by Dantas et al (2016). The colour measurements of the green stage revealed that the epicarp was green (ho=108.9), dull (C*=26.4) and slightly bright (L*= 39.9) compared to the ½ green stage which was close to yellow (ho=93.7), less dull (C*=34.4) and brighter, and in the ¾ ripe stage, where fruits displayed an angle hue approaching orange (ho= 75.3) with a chromaticity of (C*= 43.4) and enhanced brightness (L*= 50.3).…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 85%
“…Colour parameters in the epicarp of Mexican plum showed significant (P<0.05) changes among the four ripening stages (Vargas et al, 2017), similar to that reported by Dantas et al (2016). The colour measurements of the green stage revealed that the epicarp was green (ho=108.9), dull (C*=26.4) and slightly bright (L*= 39.9) compared to the ½ green stage which was close to yellow (ho=93.7), less dull (C*=34.4) and brighter, and in the ¾ ripe stage, where fruits displayed an angle hue approaching orange (ho= 75.3) with a chromaticity of (C*= 43.4) and enhanced brightness (L*= 50.3).…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 85%
“…The cashew tree is a tree native from Tropical America, producer of edible nuts and succulent stems (pseudofruits) widely consumed by the population of many countries (Leitão et al 2013;Muianga et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…umbu-cajá fruits (Spondia sp.) had measures similar to those of E. cibrata, with transversal diameter of 2.34 cm and longitudinal diameter of 2.99 cm (Dantas et al, 2016 Chitarra and Chitarra (2005) and Pinheiro (2008) described maximum increase in the surface of the cell walls, consequently the largest diameters, which may also coincide with physiological maturation. Borges et al (2010) reported that the growth of pitanga do cerrado (E. calycina) was stopped at the final maturation stage, similar to E. cibrata.…”
Section: G a S Diniz Et Almentioning
confidence: 67%
“…Borges et al (2010) reported that the growth of pitanga do cerrado (E. calycina) was stopped at the final maturation stage, similar to E. cibrata. the shape index verified for E. cibrata measured 0.98 and this relation gives a slightly elliptic rounded aspect, differing from other myrtaceae such as umbu-cajá, which presents ovoid shaped (DaNtaS et al, 2016). Chitarra and Chitarra (2006) reported that the rounded shape of fruits is an important feature for industries.…”
Section: G a S Diniz Et Almentioning
confidence: 94%
See 1 more Smart Citation